Mass extinctions and the climate - Pacheco, José Antônio de Freitas (Cadernos de Astronomia, 2025)
In this article are discussed the main causes suspected to be responsible for the massive extinction of species during the last 600 million years of the Earth’s history. Generally, cosmic catastrophes and volcanism have been invoked as the main reasons. However, in the present days, there is a consensus among experts that these extinction episodes are due to multiple causes, which modify the habitat, in particular the climate, in a short timescale. Consequently, species do not have enough time to adapt themselves to the new environment and disappear. There are indications that we are in the dawn of a new massive extinction that may have severe implications for the surviving of the humanity.